Preparation and Characterization of Calcium Sulfoaluminate Based Engineered Cementitious Composites for Rapid Repairing of Concrete Member - Lv, Leyang; Hong, Xin; Ding, Zhu; Ma, Xu; Li, Hongfeng (Frontiers in Materials, 2020)
In this work, quick hardening and high early strength engineered cementitious composites (ECC) was developed by using calcium sulfoaluminate (CSA) cement as the matrix material. The optimal mix design of CSA-ECC was studied with emphasis on the properties of fluidity and mechanical properties. It was found that CSA cement incorporated with 2% polycarboxylate-based superplasticizer (PSP), 1 % ultra-high-molecular weight polyethylene (UHMWPE) fiber and with cement to sand ratio of 0.5 shown the best performance in terms of fluidity, flexural strength and compressive strength. The fracture energy, tensile strength and strain capacity of CSA cement was significantly improved by proper mixing of UHMWPE fiber. After that, the performance of CSA-ECC in rapid repairing of concrete members was characterized. The experimental results suggest that the CSA-ECC has good bonding strength to the concrete matrix. Compared with plain concrete members, both flexural and compressive strength of concrete members were significantly reinforced after 1, 3 and 28d when CEA-ECC was applied as rapid repairing coating.